SINTREN ART SHOW : THE ANALYSIS OF THE DECLINING OF HISTORICAL AWARENESS HAPPENING IN THE COASTAL BORDER OF WEST JAVA AND CENTRAL JAVA AND ITS CONTRIBUTION TO THE HISTORY LEARNING - Supardan, Dadang (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
The study was based on research concerning the declining of historical awareness in the development of Sintren art that has been increasingly marginalized by the globalization, happening particularly in the coastal border of West Java and Central Java. This study uses a combination of historical-ethnographic methods, and for the data collection techniques the study uses observation, interview, and document study. The research results are as follows: (1) The origin of the words â€œsinyoâ€ means â€œyouthâ€ and â€œtrennenâ€ means â€œexercise in Sintren art. There is another word like â€œsesantrianâ€ which means â€œstudents play lais mimic, or debus, ubrug rudat using the magicalâ€. This Sintren was first created when the habits of the mothers and their children in the time of waiting for their husbands/fathers to come home from fishing in the sea. Instead of sleeping in the afternoon, it was better for them- the fishermen who just stayed in the house, to initiate this Sintren game. (2) The purpose of this Sintren art show at the first time was just as a habit of some women and their children who were waiting for their husbands/fathers to come home from fishing in the sea, to then, developed into a sacred game including the ceremonies for asking rain during the long drought, and served as a means of entertainment (3) Sintren art stages include (a) preparation phase: including gamelan and clothing design, and (b) staging (Sintren, Bodor and Sinden/ Singer). (4) The philosophical contribution values of the Sintren performing arts to the history education, Sintren is basically appreciated as an identity art, reflecting local delicacy, resignation, rules and norms as well as a leader in the whole performance, (5) Efforts to maintain and develop the Sintren art in other areas, especially in the Kasepuhan Cirebon Palace where annual performances of traditional arts, especially, Sintren from various regions are often performed.